Wireless based Smart Parking System using Zigbee - Sulaiman, Hamzah Asyrani; Meor Said, Maizatul Alice; Othman, Mohd Azlishah; Mohd Afif, Mohd Fareez (Engg Journals Publications, 2013)
One of main issues of developing big parking space for shopping complexes, office complexes and other types of building that requires large parking space is to notify the visitors of occupied and nonoccupied parking space. Most of the visitors might spending up to 30 to 45 minutes just to find an empty parking space. In most recent technology, some parking lot system offered a system that could automatically count when the car entering the empty car space and blocking an infrared signal thus notify the system to count for it. However, this type of sensors actually has an increase of budgeting in order to install and to be maintained. In this project, we have developed a unique solution by providing cost effective solution by using Zigbee technology in parking lot system technology. Instead of using and maintain cable that need to be installed at the ceiling of the parking lot, we developed a system that use wireless technology of Zigbee and it could notify the visitors of empty and non-empty parking lot.